Efforts to Improve Student's Learning Outcomes Through the Problem Based Learning Model - Yuyun Bahtiar; Panca Indah Kusmira Zebua; Sri Ramadhani; Iin Baroroh Ma'Arif; Luluk Choirun Nisak Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research was motivated by the low learning outcomes of fifth-grade students at Public Elementary School 071052 Mondrali. Based on the analysis conducted, the teacher found that the low student performance was due to their lack of understanding of the material being taught, which resulted from the monotonous teaching method, namely, lecturing. This condition caused students to be less actively involved in the learning process. In addition, the teacher did not use teaching media that could engage students' interest, making the lessons less appealing. As an improvement effort, the researcher applied the Problem-Based Learning (PBL) model. The aim of this research was to determine whether the implementation of the PBL model can improve the social studies learning outcomes of fifth-grade students at Public Elementary School 071052 Mondrali. The method used in this study was a quantitative method with percentage formulas. The results show an increase in student learning outcomes in each cycle. In the pre-cycle, the initial data showed that only 9.09% or 1 student passed the learning process. However, in cycle 1, the percentage of students who passed increased to 27.3% or 3 students, and in cycle 2, it reached 100%, with all students successfully passing the social studies lesson on natural and man-made features in Indonesia.